Lower size at maturation reduces somatic yield in pond reared stunted yearlings of rohu Labeo rohita (Hamilton) - Ravi, Charan; Padinhatepurayil, Suresh Babu; Razvi, Sabir Hussaine; Gundaboina, Venugopal; Anirudhan, Anuraj (Indian Journal of Fisheries, 2012)
Presently in Andhra Pradesh majority of the carp farmers use stunted yearlings as the stocking material owing to their better performance in terms of growth, survival, disease resistance and the ease of availability throughout the year. But many of the farmers reported the problem of maturation at smaller size leading to reduced growth performance of stunted fishes. In the present study, variation in the gonado-somatic index (GSI) and final somatic yield of stunted rohu females has been compared with that of normal female brooders and stunted males. The GSI of stunted females was almost 1.6 times higher than normal females and the somatic yield was significantly lower (p< 0.05).